A game theory approach for UAV-based flying access networks. (26th October 2020) - Garmani, Hamid; Omar, Driss Ait; Amrani, Mohamed El; Baslam, Mohamed; Jourhmane, Mostafa
In recent years, unmanned aerial vehicles (UAV) ad-hoc network has been receiving enormous attention from the research community, since they represent a new potential market. One promising application is to use UAVs in wireless communications field as a flying base station to extend coverage and to provide high-quality network connectivity. In this paper, we model and analyse the interactions in price, beaconing duration and quality of service among UAV. A full analysis of the game outcome, in terms of equilibrium price, equilibrium quality of service and equilibrium beaconing duration, is derived. Then we analyse the existence and uniqueness of the Nash equilibrium point under some conditions. Furthermore, we provide a learning algorithm that ensures convergence of the considered UAV with its unique Nash equilibrium operating point in a fast and distributed fashion. Finally, numerical investigations offer promising insights on how the game parameters should be chosen to efficiently control the game.